(3OQGSI aj GdCef GdSjHQGfjs - (3eMeO LGSe(B, (3Ydi Gddgs ((3YeGf (B;(3YeGf(B:s (3OGQ CeLO ddfTQ h GdJhRjY (B;(3EHUGQ fGTQhf h ehRYhf(B,s, 2023)
(3GdJfGaS GdeYdheGJj Hjf GdhdGjGJ GdeJMOI GdCeQjcjI hGdUjf(B: (3OQGSI aj GdCef GdSjHQGfj(B" (3gh Yed jJYeb aj GdUQGY GdeJRGjO Hjf GdbhJjf GdYXejjf, GdhdGjGJ GdeJMOI hGdUjf, aj GdeLGd GdQbej(B. (3jSdW GdcJGH GdVhA Ydi GdCHYGO GdeJYOOI dgPG GdJfGaS, HOkAG ef GdJLSS GdEdcJQhfj hMJi GdgLeGJ GdSjHQGfjI GdJj JSJgOa GdHfjI GdJMJjI GdMjhjI(B. (3ceG jSJcTa GdcJGH GdOhQ GdeMhQj GdPj jdYHg GdCef GdSjHQGfj aj gPg GdeYQcI, MjK CUHM MeGjI GdHjGfGJ hGdHfjI GdJMJjI GdQbejI eSCdI Cef bhej HGdZI GdCgejI(B. (3YdGhI Ydi Pdc, jMdd GdcJGH GdBKGQ GdeJQJHI Ydi gPG GdJfGaS Ydi GdYdGbGJ GdOhdjI, hjSdW GdVhA Ydi GdJMOjGJ hGdaQU GdJj JfJXQ GdYGde aj GdeSJbHd GdQbej(B.s
(3GdGNJUGQJ U(B.13 (3GdedGMb U(B.205 (3GdeQGLY U(B.177s
Keywords: (3GdYdGbGJ GdOhdjI(B- (3GdGef GdSjHQGfj(B- (3GdhdGjGJ GdeJMOI GdGeQjcjI h GdUjfs